Self-directed e-learning-based mental health interventions to improve post-covid-19 pandemic health worker resilience and well-being - Hizriansyah, Hizriansyah; Sirajunnasihin, Sirajunnasihin; Qudsi, Jihadil (Science Midwifery, 2024)
The purpose of this study is to assess the efficacy of self-directed e-learning-based mental health interventions in improving the resilience and well-being of health workers after the COVID-19 pandemic at the Madapangga Health Center in Bima Regency. The sampling technique used is nonprobability convenience sampling, where samples are selected based on the availability and willingness of health workers who take part in training and complete pre- and post-training evaluations. The course is divided into five modules covering the following topics: introduction to mental health and resilience, stress management, psychological resilience, self-care and implementation. A total of 128 people completed the program, with 91 people taking part in pre and post-training assessments. Data were collected using questionnaires with Likert scales to test knowledge and measure positive behaviors and well-being. To detect significant changes before and after the intervention, the data were analyzed using STATA 16 software and paired t-tests. Post-intervention results showed significant improvements in self-care behavior, stress management, and overall well-being. An increase in resilience scores was positively correlated with better job performance and psychological health (p < 0.000). This study shows that self-directed e-learning is effective in improving resilience and well-being of healthcare workers, especially in stress management and self-care. The program is flexible and easily accessible, especially for healthcare workers in areas with limited access to mental health services. Further research is recommended to include a larger sample sizes, long-term follow-up, and exploration of intervention components